Half a Century of Temperate Non-Forest Vegetation Changes: No Net Loss in Species Richness, but Considerable Shifts in Taxonomic and Functional Composition - Klinkovská, Klára; Sperandii, Marta Gaia; Knollová, Ilona; Danihelka, Jiří; Hájek, Michal; Hájková, Petra; Hroudová, Zdenka; Jiroušek, Martin; Lepš, Jan; Navrátilová, Jana; Peterka, Tomáš; Petřík, Petr; et al. (Global change biology, 2025)
In recent decades, global change and local anthropogenic pressures have severely affected natural ecosystems and their biodiversity. Although disentangling the effects of these factors is difficult, they are reflected in changes in the functional composition of plant communities. We present a comprehensive, large-scale analysis of long-term changes in plant communities of various non-forest habitat types in the Czech Republic based on 1154 vegetation-plot time series from 53 resurvey studies comprising 3909 vegetation-plot records. We focused not only on taxonomic diversity but also on the functional characteristics of communities. Species richness of most habitat types increased over time, and taxonomic and functional community composition shifted significantly. Habitat specialists and threatened species became less represented in plant communities, indicating a decline in habitat quality. The spread of trees, shrubs, tall herbaceous plants, strong competitors, and nutrient-demanding species in all non-forest habitats, coupled with the decline of light-demanding species, suggests an effect of eutrophication and natural succession following the abandonment of traditional management. Moreover, we identified specific trends in certain habitats. In wetlands, springs, and mires, moisture-demanding species decreased, probably due to drainage, river regulations, and increasing drought resulting from climate change. Dry grasslands, ruderal, weed, sand, and shallow-soil vegetation became more mesic, and successional processes were most pronounced in these communities, suggesting a stronger effect of abandonment of traditional management and eutrophication. In alpine and subalpine vegetation, meadows and mesic pastures, and heathlands, insect-pollinated species declined, and the proportion of grasses increased. Overall, these functional changes provide deep insights into the underlying drivers and help conservationists take appropriate countermeasures.
Keywords: zachování přírodních zdrojů; biodiverzita; vascular plants; Climate Change; Conservation of Natural Resources; klimatické změny; habitat specialists; biodiversity change; functional traits; rostliny; drought; mesophilization; Czech Republic; Biodiversity; eutrophication; Plants; succession; ekosystém; Česká republika; Ecosystem